The challenges of Crowdsourcing as one of the ways to realize participatory democracy in Iran's administrative law system - Mohmmad Javad Hosseini; Mojtaba Hemmati (دانشنامه حقوق اقتصادی)
Participatory democracy is a new type of democracy that emphasizes the public participation of citizens in all public areas of society administration and considers elections as a means to choose rulers as one of the forms of participation. In this type of democracy, the citizens are decision-makers, and activists in the public administration of the society, along with managers and rulers. they participate in the administration of public affairs through polls, internet comments, elections, referendums, crowdsourcing, law proposals, public budget approvals, policy proposals, etc. This broad participation is manifested in all aspects of life and includes culture, politics, economy and public administration. In this article, in a descriptive-analytical way and by collecting information through a library, the effects of crowdsourcing in economic affairs for the realization and continuation of participatory democracy in the administrative law system of the Islamic Republic of Iran and its challenges and solutions have been discussed. This article conclude that although in recent years, positive and effective steps have been taken for the public participation of citizens from the view point of constitutional law, but from the view point of the administrative law , due to the conflicts between the interests of managers and the people and defects in the cycle and process of crowdsourcing, until the realization of participatory democracy in the fields of Economic, social and cultural, there is a long distance ahead of the Iranian society.